PELATIHAN PENGEMBANGAN IDE BISNIS DAN BUSINESS MODEL CANVAS (BMC) UNTUK MENUMBUHKAN JIWA INOVATIF DAN KREATIF SISWA SMK NEGERI 1 BAWEN - Ahmad Sahri Romadon; Asah Wiari Sidiq; Citra Rizkiana; Yeremia Wijayanto (Fokus ABDIMAS, 2026)
The development of the digital economy and the creative economy requires vocational high school (SMK) graduates to possess not only technical competencies but also creative, innovative, and entrepreneurial thinking skills. SMK Negeri 1 Bawen, as a vocational education institution, is oriented toward graduates' job readiness. However, initial observations found that students' orientation is still predominantly as job seekers, their business ideas are unstructured, and their understanding of business planning is still limited. Furthermore, the use of digital media for economic activities is not optimal, even though students are quite familiar with technology. This community service program aims to foster students' innovative and creative spirit through training in business idea development and the preparation of a Business Model Canvas (BMC). The implementation method is carried out through three main stages: preparation, implementation, and evaluation and reporting. The implementation stage includes strengthening the entrepreneurial mindset, exploring problem-based business ideas, training in the nine elements of the Business Model Canvas, practicing developing business models in groups, and practicing presentations. Evaluation is carried out through pre- and post-tests to measure improvements in understanding, observing student participation, and assessing the quality of the resulting business models. The results of the activity showed that the training was able to improve participants' understanding of entrepreneurship and the Business Model Canvas (BMC). The training was attended by 32 students from SMK Negeri 1 Bawen, specializing in Food Crop and Horticulture Agribusiness (ATHP). The pre-test results showed a level of understanding of participants at 20%, while the post-test results increased to 70%, resulting in an increase of 50 percentage points. In addition, all groups of participants successfully compiled a Business Model Canvas (BMC) based on the business ideas they developed. This activity also succeeded in improving creativity, communication skills, teamwork, and participants' confidence in developing and presenting business ideas.   Keywords: innovation, creativity, business model canvas